VA Mycorrhizal Status in Wheat Cultivar 306 under Different Phosphorus Concentration - Vyas, Deepak (Indian Journal of Agroforestry, 2020)
A study on effect of different concentration of phosphorus on root colonization VAM fungi and plant growth of wheat was taken up. The data showed that lower concentration of 5 kg ha-1 phosphorus was optimum, which recorded greater colonization of roots and increased arbuscules and vesicles resulted in best plant growth and early yield. As the concentration of phosphorus was increased, we observed gradual decline in root colonization, reduced plant growth and lesser yield. From the rhizospheric region of the wheat roots 15 VAM fungi were isolated and identified. Out of 15 VAM fungi 7 belong to family Glomaceae followed by Acaulosporaceae 5 spp. and 3 species belong to Gigasporaceae.